Grãos em carbonatos marinhos cretácicos da Bacia Potiguar: formações Ponta do Mel e Jandaíra - Okubo, Juliana [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This work aims to identify and photograph grains that compose important Cretaceous carbonate units of the Potiguar Basin, represented by the Ponta do Mel and Jandaíra formations (Albian-Campanian). Petrographic investigation of thin sections was essential. The samples studied come from wells and surface samples from the collection UNESPetro – UNESP, Rio Claro. In the Ponta do Mel Formation, the grains consist of ooids, oncoids, peloids and bioclasts. Regarding to the identified bioclasts, the solenoporacean red algae, mollusks (bivalves and gastropods), echinoids, foraminifera, ostracods and worms were the dominant elements. In the Jandaíra Formation, the grains are composed by ooids, peloids and bioclasts, which are represented by green algae, mollusks (bivalves and gastropods), benthic foraminifera miliolids, worms, echinoderms and ostracods. The grains found in the Ponta do Mel Formation are somewhat similar to those found in the Jandaíra Formation, with the exception of calcareous algae. The subsurface material from the Ponta do Mel Formation is derived from the upper part of the unit, representing marine high-energy carbonates, which also contains ooids and Trocholina. The samples of Jandaíra Formation, collected in outcrops, often contain green algae, mollusks and miliolids, and come from inner shelf and lagoon facies previously described

O presente trabalho visa identificar e fotodocumentar os principais grãos que compõem parte das duas mais importantes unidades carbonáticas cretácicas da Bacia Potiguar, representadas pelas formações Ponta do Mel e Jandaíra (Albiano-Campaniano). Para tal estudo, a investigação petrográfica de lâminas delgadas constituiu elemento essencial. As amostras estudadas provêm de amostras de poços e de superfície, pertencentes à coleção UNESPetro – UNESP, campus de Rio Claro. Na Formação Ponta do Mel, os grãos encontrados consistem basicamente em oóides, oncóides, pelóides e bioclastos. Com relação aos bioclastos identificados, destacam-se as algas vermelhas solenoporáceas, moluscos (bivalves e gastrópodes), equinóides, foraminíferos, vermes e ostracodes. Já na Formação Jandaíra, os grãos encontrados consistem basicamente em oóides, pelóides e bioclastos. A maioria dos bioclastos encontrados nesta formação consiste em algas verdes, moluscos (bivalves e gastrópodes), foraminíferos bentônicos miliolídeos, vermes, ostracodes e equinodermos. Os tipos de grãos encontrados na Formação Ponta do Mel são, de certo modo, similares aos encontrados na Formação Jandaíra, com exceção das algas calcárias. O material da Formação Ponta do Mel deriva da parte superior da unidade, representando elementos de um pacote carbonático marinho de alta energia, que também contém oóides e Trocholina. As amostras da Formação Jandaíra emersa, frequentemente contendo algas verdes, moluscos e miliolídeos, provêm de fácies de plataforma interna e lagunares já descritas previamente
Keywords: Rochas sedimentares; Petrologia; Rochas carbonaticas; Carbonatos; Bioherma; Potiguar, Bacia (RN); Sedimentary rocks; Petrology; Carbonate rocks; Carbonates; Bioherms